2012
DOI: 10.1093/europace/eus316
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of implantable cardiac defibrillators for treatment of ventricular arrhythmias in patients with cardiac sarcoidosis

Abstract: Patients with CS and ICDs are at high risk for ventricular arrhythmias. This population also has high rates of inappropriate shocks and device complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
97
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 17 publications
6
97
2
3
Order By: Relevance
“…We think that the late observations on the predictive value of myocardial LGE, summarized in Table 5, call for a reevaluation of the recommendation at this point. Importantly, LGE predicted cardiac events despite normal or mildly reduced LV function,11 and in the study by Ise et al12 and in our study, it even outperformed LVEF, the key prognostic factor in CS reported previously 1, 2, 8, 24, 29. It is worth discussing whether some definition of myocardial LGE, for example, extent ≥22% of LV mass or involvement of the RV wall or involvement of ≥9 of 29 combined LV and RV segments (Table 5), should be added as a new or strengthening indication for an ICD in patients with CS and normal or mildly reduced LV function.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…We think that the late observations on the predictive value of myocardial LGE, summarized in Table 5, call for a reevaluation of the recommendation at this point. Importantly, LGE predicted cardiac events despite normal or mildly reduced LV function,11 and in the study by Ise et al12 and in our study, it even outperformed LVEF, the key prognostic factor in CS reported previously 1, 2, 8, 24, 29. It is worth discussing whether some definition of myocardial LGE, for example, extent ≥22% of LV mass or involvement of the RV wall or involvement of ≥9 of 29 combined LV and RV segments (Table 5), should be added as a new or strengthening indication for an ICD in patients with CS and normal or mildly reduced LV function.…”
Section: Discussionsupporting
confidence: 73%
“…Finally, ICD “may be considered” (class 2b indication) in patients with LVEF between 36% and 49% and/or RVEF <40%. The last recommendation was based mainly on 3 cohorts of CS patients with an ICD showing that ICD therapies were common, even in patients with mildly reduced LVEF 2, 24, 28. The value of myocardial LGE as an indication for an ICD in patients with normal LVEF was considered but dismissed by the experts 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is possibly due to the mixture of scar and active inflammation in many patients. As an example, CS patient cohorts seem to have higher rates of ICD therapies than other patients (42,43). The 2014 Heart Rhythm Society consensus document ( Fig.…”
Section: Ventricular Arrhythmiasmentioning
confidence: 99%
“…It has been reported that VTs are associated with reduced LVEF or a history of VTs in CS patients. 5,31,32 It was reported that delayed enhancement in the right ventricle on cardiac MRI is related to VTs in CS patients with preserved LV function and no history of VTs. 31 These findings may indicate the existence of the reentrant mechanisms for VTs.…”
Section: Positive Gallium Scintigraphy As a Factor Correlating With Vtsmentioning
confidence: 99%